Решите уравнение (х²-9)²+(х²+х-6)²=0

elenaklass1 elenaklass1    3   26.09.2019 16:10    1

Ответы
fotafoti fotafoti  08.10.2020 20:34
(х²-9)²+(х²+х-6)^2=0
(х^2-9)^2=(х^2+х-6)^2
х^2-9=х^2+х-6
х^2-х^2-х=-6+9
-х=3|*(-1)
х=-3
ПОКАЗАТЬ ОТВЕТЫ
auutumn1 auutumn1  08.10.2020 20:34
Сразу пишу продолжение.
x²+x-6=a(x-x₁)(x-x₂)
x²+x-6=(x-2)(x+3)
D=1²-4*1*(-6)=1+24=25>0, 2 korna
x₁=-1+5/2=2
x₂=-1-5/2=-3
((x-3)(x+3))+((x-2)(x+3))²=0
(x-3)²(x+3)²+(x-2)²(x+3)²=0
(x+3)²((x-3)+(x-2))=0
(x+3)²=0       ((x-3)²+(x-2)²)=0
x+3=0            x²-6x+9+x²-4x+4=0
x=-3               2x²-10x+13=0
                       D=(-10)-4*2*13=100-104=-4<0 Kornei net
Otvet:-3
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра